THE POINT OBJECT’S IMAGE FORMING RAY MODEL - Sergeev, Ju. A.; Sukhov, P. P. (Одеські астрономічні публікації, 2017)
Light wave front’s distortions are commonly explained by atmosphere turbulence. But Anler equation solution’s analysis shows that distributed homogeneous medium even in the absence of turbulence makes nonlinear transformation of coordinates as well as ray’s entry angles to the telescope’s optical system (rays’ trajectory is a screw-like line).